Analisis Pengendalian Kualitas Produk dengan Menggunakan Metode Six Sigma di Lini Electrolytic Cleaning Line (ECL) - Bahari, Alfin; Shofa, M. Jihan (Jurnal INTECH Teknik Industri Universitas Serang Raya, 2017)
A company engaged in steel, in its production activities still experienced the highest quality loss with disability in the line of Electrolytic Cleaning Line (ECL) with a percentage of disability of 16%, quality that meets company standards of 80%. The purpose of this study is to determine the baseline performance, identify the causes of disability and propose corrective action plans. This study uses the Six Sigma method that goes through the stages of analysis, namely Define, Measure, Analyze, Improve. The results of data processing, it can be seen that the process DPMO value in the Electrolytic Cleaning Line (ECL) line is 53,827,270 with a sigma level value of 3.11. From the identification of dominant CTQ, it can be seen that the CTQ that often occurs is a type of Soft Eyes. Therefore, for now, Soft Eyes is a priority for improvement. Based on the analysis of the causes of Soft Eyes using Failure Mode And Analysis (FMEA) obtained from the description of the process produces the highest Risk Priority Number (RPN) that is in human factors of 504. Since human factors are the primary cause, the company supervises the operator when doing work, to prevent unwanted defects in the product.